Exploring professionals' motivation to lead: a cross-level study in the healthcare sector - Mascia, D.; Dello Russo, S.; Morandi, F. (International Journal of Human Resource Management, 2015)
The extant leadership research has paid increasing attention to the concept of motivation to lead (MTL) as an individual construct that strongly affects leadership processes and behaviors. However, despite its importance, scant knowledge is available about how individual characteristics and organizational structural features interact in influencing MTL in professional-based organizations. This article contributes to this line of research by adopting a multilevel perspective to study the MTL among individual professionals in the healthcare sector. We collected data from a sample of 791 physicians nested in 44 departments belonging to 27 hospitals. Using the hierarchical linear model, we tested the impact of individual and organizational variables on the motivation of physicians to engage in managerial positions. Our findings demonstrate that the physicians' MTL was positively associated with their individual self-efficacy. Departmental decentralization interacted with this self-efficacy, such that the effect of self-efficacy on the MTL was significantly lower when decentralization was high. We discuss the implications of these findings for human resource management and organizational (re)design within professional organizations.